The Nativity Wealth Gap in Europe: a Matching Approach - Irene Ferrari (Global Labor Organization (GLO), 2019)
This paper uses a matching method to provide an estimate of the nativity wealth gap among older households in Europe. This approach does not require imposing any functional form on wealth and avoids validity-out-of-the-support assumptions; furthermore, it allows not only the estimation of the mean of the wealth gap but also its distribution for the common-support subpopulation. The results show that on average there is a positive and significant wealth gap between natives and migrants. However, the average gap may be misleading as the distribution of the gap reveals that immigrant households in the upper part of the wealth distribution are better off, and those in the lower part of the wealth distribution are worse off, than comparable native households. A heterogeneity analysis shows the importance of origin, age at migration and citizenship status in reducing the gap. Indeed, households who migrated within Europe, those who moved at younger ages rather than as adults and those who hold the citizenship of the destination country display a wealth gap that is rather consistently lower over the entire distribution.
Keywords: D31; J15; E21; 330; Migrants; Natives; Wealth; Gap; Propensity Score Matching